CALCULATION OF ECONOMIC EFFICIENCY OF USING VARIABLE FREQUENCY DRIVE IN PUMPING UNITS IN UNDERGROUND LEACHING TECHNOLOGY OF MINERAL RESOURCES - Kurbonov Oybek Muhammadqulovich; To'xtashev Alisher Baxodirovich; Istamov Zafarjon Vohid o'g'li; Abdixakimova Malika Amir qizi (Web of Journals Publishing, 2025)
The article discusses adequate assessment of the energy efficiency of using a variable frequency drive in pumping units in the technology of underground leaching of minerals, energy-efficient control methods, taking into account the specific features of the technology and design features of electric drives of pumping units used in the technology of underground leaching.
Keywords: Pump, energy saving, adjustable electric drive, energy efficiency, energy consumption, fictitious pressure.